2009
DOI: 10.1007/s11695-008-9773-7
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea–Hypopnea Syndrome—The Role of Bariatric and Maxillofacial Surgeries

Abstract: Obstructive sleep apnea-hypopnea syndrome (OSAHS) is a complex disease with multifactorial etiology. It is marked by the occurrence of apnea and hypopnea events caused by repeated obstructions of the upper airways. OSAHS is strongly associated with obesity, and the prevalence of this disease in morbidly obese patients is very high. Nevertheless, not all patients with OSAHS are obese, and for this reason, there may be other anatomical predispositions to airway collapse. In obese patients, fatty deposition in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Patients with OSA have been shown to have increased preoperative risk and specific perioperative measures have to been taken [4, 23]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with OSA have been shown to have increased preoperative risk and specific perioperative measures have to been taken [4, 23]. …”
Section: Discussionmentioning
confidence: 99%
“…The exact pathophysiology of OSA in obese patients remains poorly understood, but it is thought that in obese patients the local fatty tissue deposition in the neck results in reduction of the lumen of the upper airway, thereby reducing airflow and inducing airway collapse [4]. …”
Section: Introductionmentioning
confidence: 99%
“…In the present study, only patients with severe obesity were analysed, as obesity has been found to be a contributing factor to the occurrence and severity of OSAHS (5–9). However, according to Fogel et al.…”
Section: Further Discussionmentioning
confidence: 92%
“…The pathogenesis of OSAHS is complex and not yet fully understood. Obesity has been confirmed to play an important role because of fatty deposition around the pharyngeal walls, which contributes towards the narrowing and collapsibility of the airway (5–8). However, not all patients with OSAHS are obese and therefore different features that cause nocturnal upper airway obstruction in obese and non‐obese patients are expected (18).…”
Section: Further Discussionmentioning
confidence: 99%
See 1 more Smart Citation